Optimal condition-based and age-based opportunistic maintenance policy for a two-unit series system - Wang, Jingjing; Makis, Viliam; Zhao, Xian (Computers & industrial engineering, 2019)
•New opportunistic policy was developed.•Both CM and age information is utilized.•Failure replacement is initiated immediately unlike in previous papers.•New policy outperforms other widely used policies.•New effective algorithm combines SMDP and NP optimization. A new optimal maintenance policy considering the condition monitoring and age information is considered for a two-unit repairable system. Unit 1 is the core component of the system, which is subject to soft failure observed only through inspections. Unit 2 is subject to hard failure and the age information representing usage of unit 2 is available. Unlike the previous maintenance models where maintenance actions can be initiated only at the inspection epochs, we assume that corrective maintenance action would be carried out immediately when unit 2 fails. Furthermore, a preventive maintenance is performed on the units if the deterioration level of unit 1 or the usage of unit 2 exceeds certain maintenance threshold for that unit. Under this maintenance strategy, when one of the two units is correctively or preventively maintained, there is an opportunity to maintain the other unit. The maintenance problem is formulated and solved in the semi-Markov decision process framework. A formula for the average maintenance cost is derived and the optimal thresholds for preventive and opportunistic maintenance of the two units minimizing the long run expected average cost are determined. A practical example of a two-unit wind turbine system is provided, and a comparison analysis with other maintenance policies shows an outstanding performance of the proposed policy.